DETERMINATION OF RATIONAL VALUE REW-SPACING OF DISKS AND OPERATING MODES OF THE SKATING RINK DISK OF THE ADAPTATION - Rakhimberdiyevich, Normirzayev Abdukayum; Davlataliyevich, Nuriddinov Akmalzhon (IJRDO -Journal of Computer Science Engineering, 2015)
The article presents an experimental study of the determination of rational parameters values between racks is determined disks, the vertical load on the disk, the translational speed of qualitative indicators of the unit. Rational values of size of disks and operating modes of a disk skating rink defined the use of a method of mathematical planning of multiple-factor experiments and the joint solution of the received regression equations.